Hysterectomy to the Unicornuate Uterus Suffering of Hematometra: Histerektomi pada Unicornuate Uterus dengan Hematometra - Cepi T Pramayadi; Imma Nurliana; Erliana Fani (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: Unicornuate uterus with rudimentary cavity is anextremely rare Mullerian duct anomaly. It is frequently misdiagnosedor under treated, since women who suffer from thiscondition tend to be asymptomatic. We aimed to report thisinteresting case and review the available background literature.Methods: Case report.Case: A thirty two-year-old nulligravid woman was presentedwith severe abdominal pain. Laparoscopic surgery demonstratedunicornuate uterus with arudimentary cavity and hematometra.Partial hysterectomy was conducted to the right rudimentaryuterus.Conclusion: Thorough diagnosis is essential to prevent thecomplications of unicornuate uterus. Unicornuate uterus withrudimentary cavity is associated with increased rate of pregnancycomplications such as preterm labor and fetal malpresentation.Pregnancy can also occurred on the rudimentary cavity and leadsto recurrent pregnancy loss. Laparoscopy is essential for confirmatorydiagnosis. Surgical intervention should be considered asthe first line therapy to avoid associated morbidity.[Indones J Obstet Gynecol 2017; 5-4: 246-249]Keywords: hematometra, hysterectomy, unicornuate uterus